ANALISIS MANAJEMEN STRATEGI PADA UKM XYZ: MODEL MATRIKS IFE EFE DAN BALANCED SCORECARD - Felix Fernando; Amberly Anadya Prames; Mandy Aileen Lius; Muhammad Ihsan Almunawar; Steven Gilbert; Lindawati Kartika (Jurnal Pijar, 2024)
Small and Medium Enterprises (SMEs) play a significant role in Indonesia's economic growth, contributing 60.5 percent to the Gross Domestic Product (GDP) and 96.9 percent to national employment. However, SMEs in Indonesia face strategic management challenges, particularly in formulating ideal goals and missions, influenced by both internal and external conditions. This study aims to analyze and determine the ideal strategic management for XYZ SME, which is one of the SMEs experiencing such issues. Data collection was conducted through interviews with the owner of XYZ SME in February 2024. The data processing methods used in this study include the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, as well as the BalancedScorecard. The results of the study indicate that: (1) the strategic management of XYZ SME is not yet ideal based on the determined Key Performance Indicators (KPIs); (2) the appropriate and ef ective strategic management improvement method for XYZ SME involves using the IFE and EFE matrices and the Balanced Scorecard, resulting in a strategic map as the output.